Contenu et contenant de la revue Développement durable & territoires (DD&T) : 20 ans de publications au croisement de la durabilité et des territoires - Christelle Audouit; Arnaud Buchs; Guillaume Schmitt (Développement Durable et Territoires)
This article presents a reflective retrospective of 20 years of publications in the journal DD&T (Sustainability & Territories). The data processing concerns 455 articles published between 2002 and the first half of 2021 and has provided two kinds of analysis. On the one hand, a content analysis to reveal the structuring themes as well as the regularities and evolutions of the discourse. On the other hand, a container analysis to highlight its evolution in terms of disciplinary, author and institutional networks. First, these analyses reveal the intensification of multidisciplinary practices and the structuring disciplines. Secondly, discourse analysis reveals the lexical forms and structuring themes as well as the place given to the articulation of empirical and theoretical/conceptual approaches. Moreover, if the review remains focused on the links between sustainability issues and territorial issues, the reference to the notion of sustainable development is strongly blurred. Thirdly, we show that the geographical coverage of the journal is increasing, both in terms of the fields covered and the institutions to which the authors belong. This is accompanied by a growing internationalisation of the journal.